HUBUNGAN SUPERVISI KEPALA RUANGAN DENGAN PELAKSANAAN FIVE MOMENTS HAND HYGIENE PERAWAT DI RUMAH SAKIT - Ismuntania Ismuntania; Indah Nursanti; Khairunnisa Batubara; Kartika Kartika (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Supervision by the ward head is one of the factors that influence nurses' compliance in carrying out their duties in the hospital. Supervision is the direct and periodic observation by superiors of the work carried out by subordinates. Then, if problems are found, direct assistance is immediately provided to resolve them. Objective: To determine the relationship between the supervision of the ward head and the implementation of the five moments of hand hygiene for nurses in the ICU Room of Tgk Chik Di Tiro Sigli Regional Hospital. Method: Using a correlation research design to see the relationship between the variables studied. The sample used was 38 patients. The results of the study: the ward head's supervision variable was predominantly good, namely 19 patients (50.0%), and the implementation of the five moments of hand hygiene variable was predominantly not implemented, namely 33 patients (86.8%). Based on the results of the statistical test, it was found that the P value <∝ (0.05) was 0.002, meaning there was a significant relationship between direct supervision and the implementation of the five moments of hand hygiene. Furthermore, the statistical test results showed a P value < ∝ (0.05), namely 0.002, indicating a significant relationship between indirect supervision and the implementation of the five moments of hand hygiene. Hospital management needs to promote handwashing to prevent nosocomial infections.